The Knitter's Bible: The Complete Handbook for Creative Knitters (David & Charles, 2004)
Combine fabulous colors and textures with twenty-five stylish designs to create striking accessories for your home. The Knitter's Bible: Afghans & Pillows features an inspiring collection of knitted projects to brighten up the home, from luxury afghans and bedspreads to functional cushions and seating. The styles vary from basic beginner projects such as cushions and chunky throws to more advanced bedspreads and textured wall hangings. Inside, you'll discover the design secrets behind each project and choose color schemes to incorporate the projects into your own interior style. Experiment with eye-catching embellishments, sumptuous yarns and easy-to-follow techniques to simply beautify your home.

Hats & Scarves: 14 Easy Fashionable Knits (Simple Knits, ,, 2012)
Patterns to keep you warm all winter-and warm the hearts of everyone on your gift list. This is an outstanding selection of knitting patterns from established designer and bestselling writer Claire Crompton, author of The Knitter's Bible and Knitter's Bible project books. Featuring strong designs across a range of styles for those who are new to knitting, all the projects included are beginner, easy, or intermediate skill level. As well as patterns and project instructions, you will find an explanation of the abbreviations used, a knitting needle conversion chart, a skill level key, a standard yarn weight chart, knitting techniques, and making-up techniques.

Mittens & Gloves: 12 Great Ways to Keep Warm (Simple Knits, ,, 2012)
Easy-to-make mittens and gloves-the coziest winter gifts, hands down! This is a fantastic selection of knitting patterns from established designer and bestselling writer Claire Crompton, author of The Knitter's Bible and Knitter's Bible project books. Featuring strong designs across a range of styles for new-to-knitting readers, all the projects included are beginner, easy, or intermediate skill level-a majority are easy. Along with patterns and project instructions, you will also find an explanation of the abbreviations used, a knitting needle conversion chart, a skill level key, a standard yarn weight chart, knitting techniques, and making-up techniques.

Blankets & Throws: 10 Great Designs to Choose From (Simple Knits, ,, 2012)
Snuggle up with these stylish patterns from the author of The Knitter's Bible! This is a gorgeous selection of knitting patterns from established designer and bestselling writer Claire Crompton, author of The Knitter's Bible and Knitter's Bible project books. Featuring strong designs across a range of styles for those who are new to knitting, all the projects included are beginner, easy, or intermediate skill level. Along with patterns and project instructions, you will also find an explanation of the abbreviations used, a knitting needle conversion chart, a skill level key, a standard yarn weight chart, knitting techniques, and making-up techniques.

Simple Knits: Bags: 12 Fun-to-Make Bags for All Occasions (Simple Knits, ,, 2012)
Stitch up fashionable and fabulous bags with patterns from the established designer and bestselling author of The Knitter's Bible. Featuring strong designs across a range of styles for the new-to-knitting market, all the projects included are either Beginner, Easy or Intermediate skill level, and the majority are Easy. As well as patterns and project instructions, you will also find an explanation of the abbreviations used, a knitting needle conversion chart, a skill level key, a standard yarn weight chart, knitting techniques and making-up techniques. Projects include: · Fake Fur Handbag · Drawstring Bag · Patchwork Shoulder Bag · Chunky Button Backpack · The Convertible Bag · Cow-Print Shopping Tote · Summer Flower Bag · Frilly Handbag · Simple Shoulder Bag · Posy Purse · Bead Trim Evening Bag · Rose Corsage Pinstripe

Simple Knits: Cushions & Pillows: 12 Easy-Knit Projects for Your Home (Simple Knits, ,, 2012)
Patterns for the coziest and cutest cushions, seating cubes, and pillows from the established designer and bestselling author of The Knitter's Bible. Featuring strong designs across a range of styles for the new-to-knitting market, all the projects included are either Beginner, Easy or Intermediate skill level, and the majority are Easy. As well as patterns and project instructions, you will also find an explanation of the abbreviations used, a knitting needle conversion chart, a skill level key, a standard yarn weight chart, knitting techniques and making-up techniques. Projects include: · Pompom Cushion · Bright Stripe Pillows · Beaded Cushions · Black and White Pillow · Vibrant Seating Cube · Fringed Ribbon Pillow · French Knitted Cushions · Blooming Rose Pillow · Diamond Pattern Pillow · Bunting Cushion

Knitted Throws & Cushions: 25 Chic, Stylish and Cosy Projects for the Home (Knitter's Bible, ,, 2008)
The established designer and bestselling author combines fabulous colors and textures with twenty-five stylish patterns that create striking home accessories. The Knitter's Bible: Knitted Throws & Cushions features an inspiring collection of knitted projects to brighten up the home, from luxury afghans and bedspreads to functional cushions and seating. The styles vary from basic beginner projects such as cushions and chunky throws to more advanced bedspreads and textured wall hangings. Inside, you'll: · Discover the design secrets behind each project and choose color schemes to incorporate the projects into your own interior style · Experiment with eye-catching embellishments, sumptuous yarns and easy-to-follow techniques to simply beautify your home Knitting for your home is a lovely way to add a touch of handmade beauty to your interiors, add drama for a party, and dress up your furniture in colors that match the seasons.

The knitter's bible (David & Charles, Distributed in North America by F & W Pub, 2004)
A reference for knitters at all levels covers key information on materials and techniques, providing a reference library of stitch patterns, color charts for a variety of creative options, and more than twenty-five illustrated projects for clothes, accessories, and home furnishings.
Introducing Yarns , Choosing Yarns , Needles and Equipment , Holding the Needles , Casting On , Introducing Knit Stitch , Binding (Casting) Off , Introducing Purl Stitch , Combining Knit and Purl , Advanced Casting On , Advanced Binding (Casting) Off , Increasing Stitches , Decreasing Stitches , Ribs , Gauge (Tension) , Knit Perfect , Lace Knitting , Fair Isle , Cables , Embossed Knitting , Short Rows , Twisted Stitches , Intarsia , Circular Knitting , Exploring Choices , Medallion Knitting , Beaded Knitting , Looped Knitting , Entrelac , Mitred Squares , Fulling , Smocking , Reading Knitting Patterns , Knitting a Garment , Other Garment Details , Adapting a Pattern , Knitting a Patterned Garment , Tassels, Fringes and Cords , Edgings , Buttons , Flowers and Leaves , Embroidery , Correcting Mistakes , Stitch Library , Knit and Purl Stitches , Gansey Patterns , Texture Stitches , Rib Stitches , Cable Stitches , Lace Stitches , Edgings , Projects , Garter Stitch Scarf , Flower Top , Striped Bag , Cable Throw , Place Mat and Coaster , Fun Children's Mittens , Rib Stitch Scarf , Short Row Cushion , Beret , Garden Plot Squares Throw , Beaded Bag , Sheep Toy , Fair Isle Baby Blanket , Scented Sachets and Cover , Lace Bags , Funnel Neck Sweater , Lace Cardigan , Baby Bootees , Dainty Knitted Trims , Drawstring Bags , Patchwork Cushion , Greetings Cards , Gift Bags , House Sampler , Intarsia Cushion , Motifs.